1995
DOI: 10.1002/ep.670140212
|View full text |Cite
|
Sign up to set email alerts
|

Integration of chemical and biological oxidation processes for water treatment: Review and recommendations

Abstract: The literature of studies which used a combination of chemical and biological degradation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
253
0
12

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(267 citation statements)
references
References 59 publications
2
253
0
12
Order By: Relevance
“…The biodegradability of the treated leachate, obtained by the BOD 5 /COD ratio, was 0.23, while the minimum value for an effective biological treatment is 0.3 (Scott and Ollis, 1995;Marco et al, 1997;Parra et al, 2002). Furthermore, the phytotoxicity tests showed that toxicity also occurs after conventional biological treatment, thus corroborating the results found by other studies on the toxicity of treated effluents (Oral et al, 2007;De Nicola et al, 2007;Bortolotto et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…The biodegradability of the treated leachate, obtained by the BOD 5 /COD ratio, was 0.23, while the minimum value for an effective biological treatment is 0.3 (Scott and Ollis, 1995;Marco et al, 1997;Parra et al, 2002). Furthermore, the phytotoxicity tests showed that toxicity also occurs after conventional biological treatment, thus corroborating the results found by other studies on the toxicity of treated effluents (Oral et al, 2007;De Nicola et al, 2007;Bortolotto et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…It can be concluded that, in addition to precipitation coagulation process, adsorptive micellar flocculation mechanism seems contribute to the removal of surfactants and organic matters from this rejection. Many authors use the ratio BOD/COD as biodegradability index (Chamarro, et al, 2001;Scott et Ollis, 1995). Table 2 shows that BOD 5 /COD ratio for initial and treated wastewaters changed from 0.16 to 0.41.…”
Section: Discussionmentioning
confidence: 99%
“…an activated sludge system (Liver et al 1993;Pere et al 1993;Scott and Ollis 1995;Nakamura et al 1997;Novak et al 1998;Sarlin et al 1999;Thompson et al 2001;Diez et al 2002;Kostamo and Kukkonen 2003;Mahmood and Elliott 2006;Agridiotis et al 2007; Chakrabari et al 2008;Elliott and Mahmood 2012;Kaluža et al 2014). Figure 9 provides a schematic illustration of a clarifier unit that would follow such treatment.…”
Section: Secondary Treatment: Activated Sludgementioning
confidence: 99%
“…Various authors have considered options of treating the process water so that it can be reused within the normal operations of papermaking (Tenno and Paulapuro 1999;Verenich et al 2000;Webb 2002;Nuortila-Jokinen et al 2004;Hubbe 2007c;Ordóñez et al 2010;Mauchauffee et al 2012;Saif et al 2013). Wider review articles and books dealing with general aspects of wastewater treatment have appeared (Scott and Ollis 1995;Thompson et al 2001;Pokhrel and Viraraghavan 2004;Singh et al 2012;Riffat 2013;Ranade 2014;Spellman 2014;Zhao et al 2014;Hopcroft 2015;Blanco et al 2016;Fatta-Kassinos et al 2016). Finally, Ince et al (2011) reviewed strategies that can be implemented in the P&P industry to prevent pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation